2010
DOI: 10.1155/2010/695104
|View full text |Cite
|
Sign up to set email alerts
|

Search for Anti-EA(D) Antibodies in Subjects with an “Isolated VCA IgG” Pattern

Abstract: The presence of an “isolated viral capsid antigen (VCA) IgG” pattern in serum is not easy to interpret without the aid of further tests, such as specific immunoblotting or a virus genome search, that often give rise to organisational and economic problems. However, one alternative is to use an enzyme-linked immunosorbent assay (ELISA) to detect anti-early antigen (EA) antibodies, which can be found in about 85% of subjects with acute Epstein-Barr virus (EBV) infections. The purpose of this work was to search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…De Paschale et al reported that 8% of 2,442 samples from immunocompetent patients, routinely screened for EBV serology using a Diasorin EIA, displayed an isolated VCA IgG profile and demonstrated that 81% of these cases corresponded to past infection and 19% to a primary infection (11,12). In the study conducted by Klutts et al, only 2.4% of the samples harbored an isolated VCA IgG profile and 66% of them corresponded to a past infection (24).…”
Section: Discussionmentioning
confidence: 99%
“…De Paschale et al reported that 8% of 2,442 samples from immunocompetent patients, routinely screened for EBV serology using a Diasorin EIA, displayed an isolated VCA IgG profile and demonstrated that 81% of these cases corresponded to past infection and 19% to a primary infection (11,12). In the study conducted by Klutts et al, only 2.4% of the samples harbored an isolated VCA IgG profile and 66% of them corresponded to a past infection (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, as high titers can be found during EBV reactivation [26] , as well as in 20%-30% of healthy subjects with past infection [2,25] and in patients with nasopharyngeal carcinoma [27] , the diagnostic use of these antibodies is still being debated. In general, a search for EA (D) IgG alone does not identify the stage of disease [43,109] , but combining these antibodies with other parameters can be useful in laboratory diagnoses [110] because it has been found that only 12% of the patients with isolated VCA IgG and past infection are EA (D) IgG positive, as against 90% of subjects with isolated VCA IgG and acute infection [111] .…”
mentioning
confidence: 99%
“…Histories and current states of individual HHV infections are reflected in the humoral response patterns to various HHV antigens. The presence of antibodies to early antigens (EAs) is usually indicative of ongoing or recent lytic infections whereas class-switched antibodies to late or latency-associated antigens often suggest past exposure ( 11 14 ).…”
mentioning
confidence: 99%